2018
DOI: 10.1016/j.neuroimage.2017.09.047
|View full text |Cite
|
Sign up to set email alerts
|

Cortical feedback signals generalise across different spatial frequencies of feedforward inputs

Abstract: Primary visual cortex (V1) has small receptive fields and processes feedforward information at a fine-18 grained spatial scale, whereas higher visual areas have larger, spatially invariant receptive fields. Therefore, 19 feedback could provide coarse information about the global scene structure or alternatively recover fine-20 grained structure by targeting small receptive fields in V1. We tested if feedback signals generalise across 21 different spatial frequencies of feedforward inputs, or if they are tuned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 41 publications
3
27
0
Order By: Relevance
“…As previously argued (Muckli et al, 2015), this observation could suggest that the feed-back signals from higher-level regions with larger receptive fields carry information that is more abstract and therefore spatially coarser than its feed-forward counterpart. While this claim is supported by a recent study directly investigating the contribution of spatial frequencies to feedback signal (Revina et al, 2018), as indicated by the size of the error bars, this finding could simply be related to noisier signal rather than an apparent coarser resolution. Moreover, as previously mentioned, we observed that decoding accuracy is differentially modulated by misalignment for feedback and feedforward signals.…”
Section: Differences Between Volume and Surface Based Misalignmentsmentioning
confidence: 71%
“…As previously argued (Muckli et al, 2015), this observation could suggest that the feed-back signals from higher-level regions with larger receptive fields carry information that is more abstract and therefore spatially coarser than its feed-forward counterpart. While this claim is supported by a recent study directly investigating the contribution of spatial frequencies to feedback signal (Revina et al, 2018), as indicated by the size of the error bars, this finding could simply be related to noisier signal rather than an apparent coarser resolution. Moreover, as previously mentioned, we observed that decoding accuracy is differentially modulated by misalignment for feedback and feedforward signals.…”
Section: Differences Between Volume and Surface Based Misalignmentsmentioning
confidence: 71%
“…Our results could be justified by the findings in de-Wit et al (2012), where top-down prediction was shown to be topologically inaccurate as it led to activity reduction in the whole of V1, rather than at the predicted location. Revina et al (2017) also found that brain patterns due to top-down modulation did not share information with the corresponding bottom-up signals. In the prediction error realm, successful prediction would lead to zero error in the higher visual areas, and thus feature gain would decrease.…”
Section: Discussionmentioning
confidence: 95%
“…The reverse hierarchy theory also suggests that top-down modulation serves to fine-tune sensory signals by means of predictions initially made using lower spatial frequency features (Hochstein and Ahissar, 2002;Ahissar and Hochstein, 2004). Furthermore, Revina et al (2017) showed that blurred stimuli can generate top-down processes that generalize to higher spatial frequencies.…”
Section: Discussionmentioning
confidence: 97%
“…Because of its latency and its polarity reversal for top versus bottom stimulation, this component is believed to reflect feedbacks from higher-level visual areas to the early visual cortex (Miller et al 2015). It was previously suggested that these feedbacks might provide information about low and high-level scene features, such as the category or the depth of the stimuli (Morgan et al 2016;Revina et al 2018). That top-bottom feedback signals are thought to modulate sensory input, providing information about the global scene structure.…”
Section: Discussionmentioning
confidence: 99%